Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.
Customized for You
we will pick new questions that match your level based on your Timer History
Track Your Progress
every week, we’ll send you an estimated GMAT score based on your performance
Practice Pays
we will pick new questions that match your level based on your Timer History
Not interested in getting valuable practice questions and articles delivered to your email? No problem, unsubscribe here.
It appears that you are browsing the GMAT Club forum unregistered!
Signing up is free, quick, and confidential.
Join other 500,000 members and get the full benefits of GMAT Club
Registration gives you:
Tests
Take 11 tests and quizzes from GMAT Club and leading GMAT prep companies such as Manhattan GMAT,
Knewton, and others. All are free for GMAT Club members.
Applicant Stats
View detailed applicant stats such as GPA, GMAT score, work experience, location, application
status, and more
Books/Downloads
Download thousands of study notes,
question collections, GMAT Club’s
Grammar and Math books.
All are free!
Thank you for using the timer!
We noticed you are actually not timing your practice. Click the START button first next time you use the timer.
There are many benefits to timing your practice, including:
Re: Interesting Absolute value Problem [#permalink]
13 Jun 2010, 06:01
9
This post received KUDOS
Expert's post
3
This post was BOOKMARKED
Hussain15 wrote:
If x + |x| + y = 7 and x + |y| - y =6 , then x + y =
A. 3 B. 4 C. 5 D. 6 E. 9
If \(x\leq{0}\), then \(x + |x| + y = 7\) becomes: \(x-x+y=7\) --> \(y=7>0\), but then \(x + |y| - y =6\) becomes: \(x+y-y=6\) --> \(x=6>0\), which contradicts the initial assumption \(x\leq{0}\). So \(x\) can not be \(\leq{0}\) --> hence \(x>0\).
Similarly if \(y\geq{0}\), then \(x + |y| - y =6\) becomes: \(x+y-y=6\) --> \(x=6>0\), but then \(x + |x| + y = 7\) becomes: \(x+x+y=12+y=7\) --> \(y=-5<0\), which contradicts the initial assumption \(y\geq{0}\). So \(y\) can not be \(\geq{0}\) --> hence \(y<0\).
So \(x>0\) and \(y<0\): \(x+|x|+y=7\) becomes: \(x+x+y=7\) --> \(2x+y=7\); \(x+|y|-y=6\) becomes: \(x-y-y=6\) --> \(x-2y=6\).
Solving: \(x=4\) and \(y=-1\) --> \(x+y=3\).
Answer: A.
I feel there is an easier way, but world cup makes it harder to concentrate. _________________
Re: Interesting Absolute value Problem [#permalink]
18 Jun 2010, 06:23
Bunuel wrote:
Hussain15 wrote:
If x + |x| + y = 7 and x + |y| - y =6 , then x + y =
A. 3 B. 4 C. 5 D. 6 E. 9
If \(x\leq{0}\), then \(x + |x| + y = 7\) becomes: \(x-x+y=7\) --> \(y=7>0\), but then \(x + |y| - y =6\) becomes: \(x+y-y=6\) --> \(x=6>0\), which contradicts the initial assumption \(x\leq{0}\). So \(x\) can not be \(\leq{0}\) --> hence \(x>0\).
Similarly if \(y\geq{0}\), then \(x + |y| - y =6\) becomes: \(x+y-y=6\) --> \(x=6>0\), but then \(x + |x| + y = 7\) becomes: \(x+x+y=12+y=7\) --> \(y=-5<0\), which contradicts the initial assumption \(y\geq{0}\). So \(y\) can not be \(\geq{0}\) --> hence \(y<0\).
So \(x>0\) and \(y<0\): \(x+|x|+y=7\) becomes: \(x-x+y=7\) --> \(2x+y=7\); \(x+|y|-y=6\) becomes: \(x-y-y=6\) --> \(x-2y=6\).
Solving: \(x=4\) and \(y=-1\) --> \(x+y=3\).
Answer: A.
I feel there is an easier way, but world cup makes it harder to concentrate.
Re: Interesting Absolute value Problem [#permalink]
18 Jun 2010, 06:28
Expert's post
GMATBLACKBELT720 wrote:
Bunuel wrote:
Hussain15 wrote:
If x + |x| + y = 7 and x + |y| - y =6 , then x + y =
A. 3 B. 4 C. 5 D. 6 E. 9
If \(x\leq{0}\), then \(x + |x| + y = 7\) becomes: \(x-x+y=7\) --> \(y=7>0\), but then \(x + |y| - y =6\) becomes: \(x+y-y=6\) --> \(x=6>0\), which contradicts the initial assumption \(x\leq{0}\). So \(x\) can not be \(\leq{0}\) --> hence \(x>0\).
Similarly if \(y\geq{0}\), then \(x + |y| - y =6\) becomes: \(x+y-y=6\) --> \(x=6>0\), but then \(x + |x| + y = 7\) becomes: \(x+x+y=12+y=7\) --> \(y=-5<0\), which contradicts the initial assumption \(y\geq{0}\). So \(y\) can not be \(\geq{0}\) --> hence \(y<0\).
So \(x>0\) and \(y<0\): \(x+|x|+y=7\) becomes: \(x-x+y=7\) --> \(2x+y=7\); \(x+|y|-y=6\) becomes: \(x-y-y=6\) --> \(x-2y=6\).
Solving: \(x=4\) and \(y=-1\) --> \(x+y=3\).
Answer: A.
I feel there is an easier way, but world cup makes it harder to concentrate.
Why when y<0 do we get -2y?
When \(y<0\), then \(|y|=-y\) and \(x+|y|-y=6\) becomes: \(x-y-y=6\) --> \(x-2y=6\). _________________
Re: Interesting Absolute value Problem [#permalink]
18 Jun 2010, 07:17
^ Wow... confusing as heck. Essentially saying that (hypothetical number here) |-3| = -(-3), thats fine. But I kept thinking you would apply this to -y and essentially make it +y since and make them both +y...
Re: If x + |x| + y = 7 and x + |y| - y =6 , then x + y = [#permalink]
02 Jul 2013, 05:38
If x + |x| + y = 7 and x + |y| - y =6 , then x + y =
can be done in 2.3 mins :
there are 4 cases to be tested : 1) x is -ve and y is -ve substituting in the equation , we get x-x+y=7 and x-y-y=6 solve for x and y we get x=20 and y=7 , so x+y=27 REJECT
2)x is +ve and y is +ve
substitute in the equation, we ger x+x+y=7 and x+y-y=6 solve for x and y we get x=6 and y=-5 ,therefore x+y=1 not on list so REJECT
3) x is -ve and y is +ve
substitute , we get x-x=y=7 and x+y-y=6 solve fo x and y we get x=6 and y=7, x+y=13 not on list so REJECT
4) x is +ve and y is -ve
substitute , we get x+x=y=7 and x-y-y=6 solve for x and y , we get x=4 and y= -1 ,x+y=3 , ANSWER CHOICE
Re: Interesting Absolute value Problem [#permalink]
05 Jul 2013, 10:19
Bunuel wrote:
GMATBLACKBELT720 wrote:
Bunuel wrote:
If \(x\leq{0}\), then \(x + |x| + y = 7\) becomes: \(x-x+y=7\) --> \(y=7>0\), but then \(x + |y| - y =6\) becomes: \(x+y-y=6\) --> \(x=6>0\), which contradicts the initial assumption \(x\leq{0}\). So \(x\) can not be \(\leq{0}\) --> hence \(x>0\).
Similarly if \(y\geq{0}\), then \(x + |y| - y =6\) becomes: \(x+y-y=6\) --> \(x=6>0\), but then \(x + |x| + y = 7\) becomes: \(x+x+y=12+y=7\) --> \(y=-5<0\), which contradicts the initial assumption \(y\geq{0}\). So \(y\) can not be \(\geq{0}\) --> hence \(y<0\).
So \(x>0\) and \(y<0\): \(x+|x|+y=7\) becomes: \(x-x+y=7\) --> \(2x+y=7\); \(x+|y|-y=6\) becomes: \(x-y-y=6\) --> \(x-2y=6\).
Solving: \(x=4\) and \(y=-1\) --> \(x+y=3\).
Answer: A.
I feel there is an easier way, but world cup makes it harder to concentrate.
Why when y<0 do we get -2y?
When \(y<0\), then \(|y|=-y\) and \(x+|y|-y=6\) becomes: \(x-y-y=6\) --> \(x-2y=6\).
Sorry, still confusing me. I understand the first y i.e. |y| = -y But y < 0, so wouldn't x + |y| - y = x - y - (-y), which would make it just x?
Re: If x + |x| + y = 7 and x + |y| - y =6 , then x + y = [#permalink]
03 Sep 2014, 10:18
Hello from the GMAT Club BumpBot!
Thanks to another GMAT Club member, I have just discovered this valuable topic, yet it had no discussion for over a year. I am now bumping it up - doing my job. I think you may find it valuable (esp those replies with Kudos).
Want to see all other topics I dig out? Follow me (click follow button on profile). You will receive a summary of all topics I bump in your profile area as well as via email. _________________
Re: If x + |x| + y = 7 and x + |y| - y =6 , then x + y = [#permalink]
27 Sep 2015, 14:44
Hello from the GMAT Club BumpBot!
Thanks to another GMAT Club member, I have just discovered this valuable topic, yet it had no discussion for over a year. I am now bumping it up - doing my job. I think you may find it valuable (esp those replies with Kudos).
Want to see all other topics I dig out? Follow me (click follow button on profile). You will receive a summary of all topics I bump in your profile area as well as via email. _________________
Re: If x + |x| + y = 7 and x + |y| - y =6 , then x + y = [#permalink]
27 Sep 2015, 23:10
1
This post received KUDOS
Expert's post
Hussain15 wrote:
If x + |x| + y = 7 and x + |y| - y =6 , then x + y =
A. 3 B. 4 C. 5 D. 6 E. 9
In such a question, you can use some brute force and get to the answer too. How long it takes depends on how quickly you observe the little things.
x + |x| + y = 7 x + |y| - y =6
Both equations yield about the same result though in one y is positive and in the other it is negative. |x| and |y| are positive and assuming x is positive, a negative y would pull down the first equation and pump up the second one to give almost equal values. The difference is very small also signifies that the negative variable might have a very small value. Since the options give the value of x + y as 3/4/5... etc, it is likely that we are dealing with small number pairs such as (4, 2), (3, 2), (4, 1) etc. Since the first equation has 7 as the result, both variables will not be even. A couple of quick iterations brought me to (4, -1). So x + y = 3 _________________
Re: If x + |x| + y = 7 and x + |y| - y =6 , then x + y = [#permalink]
24 Oct 2015, 06:05
VeritasPrepKarishma wrote:
Hussain15 wrote:
If x + |x| + y = 7 and x + |y| - y =6 , then x + y =
A. 3 B. 4 C. 5 D. 6 E. 9
In such a question, you can use some brute force and get to the answer too. How long it takes depends on how quickly you observe the little things.
x + |x| + y = 7 x + |y| - y =6
Both equations yield about the same result though in one y is positive and in the other it is negative. |x| and |y| are positive and assuming x is positive, a negative y would pull down the first equation and pump up the second one to give almost equal values. The difference is very small also signifies that the negative variable might have a very small value. Since the options give the value of x + y as 3/4/5... etc, it is likely that we are dealing with small number pairs such as (4, 2), (3, 2), (4, 1) etc. Since the first equation has 7 as the result, both variables will not be even. A couple of quick iterations brought me to (4, -1). So x + y = 3
Hi Karishma,
I tried another approach, but got stuck - can you hep me solve by this method? x + |x| + y = 7 => x + y = 7 - |x| => Whatever be the value of x, |x| will be always non-negative => x + y has to be less than 7 => This eliminates option E x + |y| - y = 6 => Now, if y is positive, then this equation becomes x = 6 => on substituting in above eqn, we get y = -5 => x+y = 1 => Not present in any of the options => y is negative => x - y - y = 6 => x - 2y = 6 => x = 6 + 2y Now x + y = 7 - |6 + 2y| If we take y = -1, we get x + y = 3 = Option A If we take y = -2, we get x + y = 5 = Option C I am getting both options here - where am I going wrong here? Or this approach incorrect? _________________
If x + |x| + y = 7 and x + |y| - y =6 , then x + y = [#permalink]
24 Oct 2015, 06:55
2
This post received KUDOS
sagar2911 wrote:
Hi Karishma,
I tried another approach, but got stuck - can you hep me solve by this method? x + |x| + y = 7 => x + y = 7 - |x| => Whatever be the value of x, |x| will be always non-negative => x + y has to be less than 7 => This eliminates option E x + |y| - y = 6 => Now, if y is positive, then this equation becomes x = 6 => on substituting in above eqn, we get y = -5 => x+y = 1 => Not present in any of the options => y is negative => x - y - y = 6 => x - 2y = 6 => x = 6 + 2y Now x + y = 7 - |6 + 2y| If we take y = -1, we get x + y = 3 = Option A If we take y = -2, we get x + y = 5 = Option C I am getting both options here - where am I going wrong here? Or this approach incorrect?
Let me try to answer.
You are making a mistake with using |6+2y|
After you get x=6+2y and substitute in equation (1), you get 6+2y+|6+2y|+y=7 ---->6+3y+|6+2y| = 7 ---> 3y+|6+2y| = 1. Now the point to note is that the 'nature' of |6+2y| changes at y=-3 and thus you need to evaluate |6+2y| for values smaller than -3 and for values greater than -3.
You have already assumed that y<0 in order to get x=6+2y, so your ranges to consider become -3 \(\le\)q y < 0 and y < -3
Case 1: -3 \(\le\) y < 0, giving you |6+2y| \(\geq\) 0 ----> 3y+|6+2y| = 1 ---> 3y+6+2y = 1 ---> 5y=-5 ---> y=-1. Acceptable value giving you x=6+2y = 4 --> x+y = 3
Case 2: y<-3 ---> |6+2y| = -(6+2y) ---> 3y+|6+2y| = 1 ---> 3y-6-2y = 1 ---> y=7 this contradicts the assumption that y<-3 , making this out of scope.
Re: If x + |x| + y = 7 and x + |y| - y =6 , then x + y = [#permalink]
24 Oct 2015, 08:52
Engr2012 wrote:
sagar2911 wrote:
Hi Karishma,
I tried another approach, but got stuck - can you hep me solve by this method? x + |x| + y = 7 => x + y = 7 - |x| => Whatever be the value of x, |x| will be always non-negative => x + y has to be less than 7 => This eliminates option E x + |y| - y = 6 => Now, if y is positive, then this equation becomes x = 6 => on substituting in above eqn, we get y = -5 => x+y = 1 => Not present in any of the options => y is negative => x - y - y = 6 => x - 2y = 6 => x = 6 + 2y Now x + y = 7 - |6 + 2y| If we take y = -1, we get x + y = 3 = Option A If we take y = -2, we get x + y = 5 = Option C I am getting both options here - where am I going wrong here? Or this approach incorrect?
Let me try to answer.
You are making a mistake with using |6+2y|
After you get x=6+2y and substitute in equation (1), you get 6+2y+|6+2y|+y=7 ---->6+3y+|6+2y| = 7 ---> 3y+|6+2y| = 1. Now the point to note is that the 'nature' of |6+2y| changes at y=-3 and thus you need to evaluate |6+2y| for values smaller than -3 and for values greater than -3.
You have already assumed that y<0 in order to get x=6+2y, so your ranges to consider become -3 \(\le\)q y < 0 and y < -3
Case 1: -3 \(\le\) y < 0, giving you |6+2y| \(\geq\) 0 ----> 3y+|6+2y| = 1 ---> 3y+6+2y = 1 ---> 5y=-5 ---> y=-1. Acceptable value giving you x=6+2y = 4 --> x+y = 3
Case 2: y<-3 ---> |6+2y| = -(6+2y) ---> 3y+|6+2y| = 1 ---> 3y-6-2y = 1 ---> y=7 this contradicts the assumption that y<-3 , making this out of scope.
Thus the only value of x+y = 3.
Excellent. Thank you dude! _________________
+1 Kudos if you liked my post! Thank you!
gmatclubot
Re: If x + |x| + y = 7 and x + |y| - y =6 , then x + y =
[#permalink]
24 Oct 2015, 08:52
The “3 golden nuggets” of MBA admission process With ten years of experience helping prospective students with MBA admissions and career progression, I will be writing this blog through...
You know what’s worse than getting a ding at one of your dreams schools . Yes its getting that horrid wait-listed email . This limbo is frustrating as hell . Somewhere...
Wow! MBA life is hectic indeed. Time flies by. It is hard to keep track of the time. Last week was high intense training Yeah, Finance, Accounting, Marketing, Economics...